P18. Effekte von Perampanel auf die Gliom-assoziierte Epilepsie. Issue 8 (August 2018) - Lange, F.; Porath, K.; Hartung, J.; Resch, T.; Weßlau, K.; Hörnschemeyer, J.; Linnebacher, M.; Schültke, E.; Kirschstein, T.; Köhling, R.
Abstract : Seizures are a well-recognized symptom of glioblastoma, and anticonvulsive treatment is common. While clinical guidelines recommend all approved anticonvulsants, so far there is a lack of data that allow a well-founded differential therapy. Based on pathophysiological knowledge about both mechanisms of glioma-associated seizures and tumor progression, it is conceivable that some certain anti-seizure medication could be more preferable than others in the sense of a combined anti-convulsive and anti-tumoral efficacy. Thus, glioma cells release glutamate via the Xc − antiport system, which appears to be a major pathomechanism of glioma-associated seizures and excitotoxicity. In addition, the proliferation and survival of the tumor cells are promoted. Therefore, anticonvulsants that attenuate glutamate-mediated receptor activation could be especially effective. In a first in vitro approach, perampanel had antiproliferative effects. In addition, AMPA receptor-mediated epileptiform activity was effectively reduced in rat glioma brain slices using perampanel. In our current studies, rat glioma cells are injected orthotopically into the neocortex of Fischer rats. Thus, both tumor disease and glioma-associated epilepsy can be simulated in a clinically relevant in vivo model. In this model, the efficacy of perampanel in combination with standard radio-chemotherapy on the survival of the animals is examined. Epileptiform activity is recorded with video EEG monitoring in vivo and additionally analyzed in an in vitro epilepsy model (Mg 2+ withdrawal, GABAA receptor inhibition). On the side of the tumor disease, the morphology of the gliomas is determined and the expression of relevant proteins is quantified. To gain further insights into the mechanisms of glutamate-mediated pathophysiology of human gliomas, patient-generated low-passage glioblastoma cell lines were established from more than 50 surgical brain tumor resectants. In 15 of these cell lines, we quantified the expression of various epilepsy-associated genes by RT-PCR. As expected, the genes SLC7A11, EAAT2, GLUL, BCAT1 and IDH1 were expressed differently in the cells. To validate these findings, four cell lines with a pro-epileptogenic phenotype were selected. In addition, the efficacy of perampanel on glutamate release and cell proliferation was tested. It could be shown that perampanel mediate an overall reduction of glutamate release cross all cell lines. With our combined in vitro and in vivo approach, we aim to investigate the efficacy of glutamate receptor antagonists such as perampanel on glioblastoma cells with respect to seizure development and tumor progression. Our results suggest that anticonvulsants that inhibit glutamate receptor activation may be particularly suitable.